Respiration activity monitoring system for any individual well of a 48-well microtiter plate. Issue 1 (December 2016) - Flitsch, David; Krabbe, Sebastian; Ladner, Tobias; Beckers, Mario; Schilling, Jana; Mahr, Stefan; Conrath, Uwe; Schomburg, Werner; Büchs, Jochen
Abstract Background Small-scale micro-bioreactors have become the cultivation vessel of choice during the first steps of bioprocess development. They combine high cultivation throughput with enhanced cost efficiency per cultivation. To gain the most possible information in the early phases of process development, online monitoring of important process parameters is highly advantageous. One of these important process parameters is the oxygen transfer rate (OTR). Measurement of the OTR, however, is only available for small-scale fermentations in shake flasks via the established RAMOS technology until now. A microtiter plate-based (MTP) μRAMOS device would enable significantly increased cultivation throughput and reduced resource consumption. Still, the requirements of miniaturization for valve and sensor solutions have prevented this transfer so far. This study reports the successful transfer of the established RAMOS technology from shake flasks to 48-well microtiter plates. The introduced μRAMOS device was validated by means of one bacterial, one plant cell suspension culture and two yeast cultures. Results A technical solution for the required miniaturized valve and sensor implementation for an MTP-based μRAMOS device is presented. A microfluidic cover contains in total 96 pneumatic valves and 48 optical fibers, providing two valves and one optical fiber for each well. To reduce costs, an optical multiplexer for eight oxygen measuring instruments and 48 optical fibers is introduced. This configuration still provides a reasonable number of measurements per time and well. The well-to-well deviation is investigated by 48 identicalEscherichia coli cultivations showing standard deviations comparable to those of the shake flask RAMOS system. The yeastHansenula polymorpha and parsley suspension culture were also investigated. Conclusions The introduced MTP-based μRAMOS device enables a sound and well resolved OTR monitoring for fast- and slow-growing organisms. It offers a quality similar to standard RAMOS in OTR determination combined with an easier handling. The experimental throughput is increased 6-fold and the media consumption per cultivation is decreased roughly 12.5-fold compared to the established eight shake flask RAMOS device.